Public Enterprise in the Limelight: a Review of the New Research Agenda in Europe and Latin America - Ascencio, Débora (Revista del CLAD Reforma y Democracia, 2021)
Despite the inescapable relevance of public enterprises in the world's economies, the researchers who have devoted themselves to their study coincide in pointing out a historiographic and conceptual void around the subject and stress the importance of promoting research that will allow the accumulation of a considerable base of empirical studies to overcome generic interpretations and develop specific bodies of theory. In this sense, considering the aforementioned vacancy and the relating degree of dispersion in the contributions, this article proposes to comprehensively review the emergence of a recent and prolific research agenda, particularly located in Europe and Latin America, with substantial findings for the study of public enterprises and whose systematization allows identifying common aspects that, so far, have been disarticulated. Among the main conclusions is the origin of public enterprises with the emergence of the Nation-States stands out. This is central to an assessment of privatizations, because the projects that defended market solutions were based on the false postulate that state-owned enterprises originate and grow only with the left-wing or interventionist governments. In addition, they provide empirical evidence that shows there is no strict coincidence between political cycles and the evolution of the growth of firms; on the contrary, their development responds to very heterogeneous factors. Based on this “ideological stigma” attached to public enterprises, a series of myths about their supposedly inefficient operation are sustained. However, the studies examined show that ownership is just one more element within the multiplicity of factors involved in business performance and highlight central aspects of public administration, such as governance, state capacities, or what that some authors call entrepreneurship, although these are still open debates, the nuances of which are systematized throughout the work. These approaches are linked to analyses of the new formats of the 21st century, very different from the traditional state monopoly, in which public and private capital appear combined and competing in liberalized international markets.
Keywords: Public Enterprises; Public Enterprises Reform; State; State Theory; Europe; Latin America